Z-scan technique to study gain properties of optically pumped media. (5th February 2018) - Semashko, V V; Akhtyamov, O R; Shavelev, A A; Rakhimov, N F; Lovchev, A V
Abstract: The opportunity to study the optical gain properties of active media using the open aperture z-scan technique without an additional probe beam is demonstrated. The method allows for the evaluation of pump-induced photodynamic process parameters in UV solid-state active media on pumping and lasing wavelengths: excited-state absorption and photoionization cross-sections of active ions, effective absorption and ionization cross-sections of color centers and recombination rates.